SEASONAL VARIATION OF SOME IMPORTANT SERUM ENZYMES ACTIVITIES IN SHEEP - Alkhayyat, A.; A. Abbas, D.; M. Said, A. (The Iraqi Journal of Veterinary Medicine, 1987)
Blood serum samples were obtained from ten normal nonpregnant ewes at mid January and mid August. The level of acetylcholine estrease (ChE). enzyme activity was estimated colorimetrically while the values of glutamete-oxaloacetate transaminase (COT), glutamate-pyruvate transaminase (GPT) and alkaline Phosphatease (A Ph) were estimated by an autoanalyzer. The results indicated significant depression in the normal values of ChE, GOT and GPT in summer season.